CONTEXTUAL EVANGELIZATION IN THE KETENGBAN TRIBE, STAR MOUNTAINS, MOUNTAIN PAPUA PROVINCE - Malyo, Tirianus (Anfa Mediatama, 2024)
There is dissatisfaction from the Researcher regarding the Evangelism service carried out by the Papuan Union Forest Service Team (PUFST), in the Ketengban Tribe, which seems to only fulfill routine, so the Researcher theoretically analyzes all service methods to obtain special attention in improving service methods that adapt to the situation and conditions in the Ketengban Tribe. The service system for people in the Ketengban tribe has not been implemented optimally, the methods used for service have not been considered and cooperation has not been created. All of this indicates the level of success of services in the Ketengban Tribe. This research aims to: (1) explain the root of the problems in the ministry of preaching the Gospel of Christ in the Ketengban Tribe; (2) finding and offering evangelistic methods to reach new souls (3) finding and offering a good quality of life for people in the Ketengban Tribe; (4). find and offer service methods to have spiritual qualities for believers in the Ketengban Tribe. The results of the research have found several appropriate methods to be used by researchers and the PUFST Mission Team to be used in the ministry of preaching the Gospel of Christ in the Ketengban Tribe. The researcher believes that the results of this research are very useful for everyone who has a longing for the ministry of preaching the Gospel of Christ to people in the Ketengban Tribe in order to reach new souls for God and teach spiritual qualities to people in the Ketengban Tribe. So that services can be carried out effectively and efficiently at the service location.